2010
DOI: 10.1111/j.1749-8198.2010.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Caring Roles and Responsibilities within the Family in Africa

Abstract: In many Sub‐Saharan African countries, the care of chronically ill, disabled or elderly relatives is usually regarded as the responsibility of family members, within a broader landscape of often overburdened healthcare systems, the expense of medical fees, very limited access to social protection and policies that emphasise home‐based care. Recent studies have demonstrated that children and youth, particularly girls and young women, take on considerable caring roles for chronically ill and elderly and young re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 72 publications
3
92
0
Order By: Relevance
“…However, younger siblings spent considerable amounts of time undertaking household chores (girls even reported spending slightly more time than their older sisters) and self care activities. For younger siblings, the category of 'community engagement' included playing and spending time with friends, which older siblings reported was more limited for them- Table 2 Young people's activities in youth-headed households (see also Evans, 2010 Maintaining social networks, seeking support from and cooperating with others, participating in neighbourhood, school, faith community, youth and NGO meetings, activities and events, playing and spending time with friends selves; 'community engagement' for them represented predominantly time spent seeking support from others and going to the church/mosque. Older and younger boys reported spending longer in community engagement activities outside the household compared to girls, reflecting conventional gender norms about the use of public and private space and boys' and young men's greater spatial mobility and freedom to engage with the wider environment (Katz, 1993).…”
Section: Time-space Routines Of Caringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, younger siblings spent considerable amounts of time undertaking household chores (girls even reported spending slightly more time than their older sisters) and self care activities. For younger siblings, the category of 'community engagement' included playing and spending time with friends, which older siblings reported was more limited for them- Table 2 Young people's activities in youth-headed households (see also Evans, 2010 Maintaining social networks, seeking support from and cooperating with others, participating in neighbourhood, school, faith community, youth and NGO meetings, activities and events, playing and spending time with friends selves; 'community engagement' for them represented predominantly time spent seeking support from others and going to the church/mosque. Older and younger boys reported spending longer in community engagement activities outside the household compared to girls, reflecting conventional gender norms about the use of public and private space and boys' and young men's greater spatial mobility and freedom to engage with the wider environment (Katz, 1993).…”
Section: Time-space Routines Of Caringmentioning
confidence: 99%
“…Comparative research with children caring for parents with HIV has revealed that children undertake broadly similar caring roles in the majority and minority worlds, although the nature of caring tasks and the time taken to perform them differs due to disparities in living standards, basic services and infrastructure (Bauman et al, 2006;Evans and Becker, 2009). Children's caring roles include supporting family members with healthcare, personal care, household chores, childcare and providing emotional and practical support (Evans, 2010). A key difference in the majority world is children's involvement in income earning activities as a replacement for the loss of a parent's/adult relative's income (Evans and Becker, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The psychological template of fixed developmental stages generates a culturally unreflective narrative about the essential nature of childhood (O'Dell et al, 2010) which is contradicted by belief systems prevalent in non-Western societies such as those of subSaharan Africa (Evans, 2010;Becker, 2007) where children and young people commonly take on caring and other roles v . The prevailing cultural template of childhood in rich societies has generated a sense that caring at 'too early' an age puts young people at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Grandmothers and aunts, in particular, but also grandfathers and uncles, often contribute extensively to children's many needs (Akintola 2004(Akintola , 2008Schatz and Seeley 2015). At the same time young people, perhaps particularly girls, contribute to their households and provide care to older persons (Evans 2010). Yet, little is known about the impact on children's wellbeing of their simultaneous receipt and provision of care from and to the older generation.…”
Section: Introductionmentioning
confidence: 99%